2019
DOI: 10.1523/jneurosci.2759-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

A Subpopulation of Amygdala Neurons Mediates the Affective Component of Itch

Abstract: Itch consists of both sensory and affective components. For chronic itch patients, the affective component of itch affects both quality of life (leading to psychological comorbidities) and disease prognosis (by promoting scratching of itchy skin). We found that acute itch stimuli, such as histamine, induced anxiety-like behavior and increased activity (c-Fos expression) in the amygdala in adult male C57BL/6 mice. Itch stimuli also increased activity in projection areas to the amygdala, suggesting that these re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 46 publications
3
44
0
2
Order By: Relevance
“…Itch, like many other somatosensations, is a complex experience consisting of sensory, emotional and motivational components. Indeed, animal studies have shown that acute pruritic stimuli can induce conditional place aversion (CPA), as well as anxiety-like behaviors, as revealed by the open field test (OFT) and elevated plus maze (EPM) assay, suggesting a negative emotional component of itch sensation [104][105][106] . As indicated by previous human functional imaging studies, multiple brain regions could be involved in processing the affective components of itch sensation 1,2 .…”
Section: Emotional Components Of Itch Sensationmentioning
confidence: 99%
“…Itch, like many other somatosensations, is a complex experience consisting of sensory, emotional and motivational components. Indeed, animal studies have shown that acute pruritic stimuli can induce conditional place aversion (CPA), as well as anxiety-like behaviors, as revealed by the open field test (OFT) and elevated plus maze (EPM) assay, suggesting a negative emotional component of itch sensation [104][105][106] . As indicated by previous human functional imaging studies, multiple brain regions could be involved in processing the affective components of itch sensation 1,2 .…”
Section: Emotional Components Of Itch Sensationmentioning
confidence: 99%
“…84,85 In an experiment in mice, histamine, chloroquine, and serotonin induced significant activation of the laterocapsular and medial divisions of the central amygdala, and the basolateral amygdala was activated as well. 86 Furthermore, injection of a gaminobutyric acid agonist into the amygdala has been shown to suppress itch in rats. 87 In another study, stress-aggravated pruritus was evoked by asking patients with neurodermatoses to think about stressful situations before magnetic resonance imaging.…”
Section: Stress Itch and The Brainmentioning
confidence: 99%
“…多个研究 发现, 压力情境会使慢性瘙痒患者的瘙痒强度增加 [48] . OFT)中小鼠在中心方框的停留时间显著减少 [49] . 这些 结果说明, 杏仁核在压力情景促进痒感受增强的过程 中承担着一定的作用 [50] .…”
Section: 当机械敏感多觉型伤害感受纤维被阻断时 组胺仍然unclassified
“…这些 结果说明, 杏仁核在压力情景促进痒感受增强的过程 中承担着一定的作用 [50] . 因此杏仁核、臂旁核、中扣 带回以及内侧前额叶也许构成了痒的情感维度环路, 驱动了抓挠行为和其他由瘙痒导致的焦虑样行为 [49] .…”
Section: 当机械敏感多觉型伤害感受纤维被阻断时 组胺仍然unclassified